The land and people of Burma - Landry, Lionel (Philadelphia : Lippincott, 1968)
An introduction to the history, religious life, and present regimentation of the Golden Land where today a traditionally happy people are experimenting with socialism.
Keywords: Burma -- Juvenile literature